Terminator : dark fate [videorecording (DVD)] - Miller, Tim, 1964-; Hamilton, Linda, 1956-; Schwarzenegger, Arnold; Davis, Mackenzie (Paramount, 2019)
A woman and a hybrid cyborg must save a young girl from a newly modified liquid terminator from the future.